Study on the Composite Performance of Sandwich Wall Panels with SGCCs - Huanzhi Jiang; Libo Xie; Fengyuan Chang; Yu Cao; Zhengxing Guo (Buildings)
This paper aims to explore the impact of different arrangements of new steel-glass FRP composite connectors (SGCCs) on the bending and composite performance of sandwich wall panels. Through monotonic loading bending tests on six full-size specimens, aspects such as their failure modes, load-deflection curves, load-strain relationships, slip between the thermal insulation layer and concrete, and composite action were analyzed. The results show that all sandwich wall panels experienced bending and ductile failure, and exhibit partial composite performance, with P4 having the best composite performance and P1 the worst. The degree of composite action is positively correlated with the flexural bearing capacity. The bending capacity mainly depends on the layout rather than the total number of SGCCs. Arranging connectors along the short side of the panel has a more significant impact, and the number of connectors at the panel’s ends has a greater influence on the composite performance. Except for P1, the theoretical value of the composite degree of the other sandwich wall panels exceeds 70%, and P4 reaches 85%. The theoretical calculations are in good agreement with the experimental results. This study provides theoretical and data support for the rational configuration of connectors in sandwich wall panels and is of great significance for building engineering applications. Meanwhile, suggestions for configuring connectors in actual engineering are also given.